Extremely female-biased primary sex ratio and precisely constant male production in a parasitoid wasp Melittobia - Abe, J; Kamimura, Y; Shimada, M; West, SA (2009)
The study of sex allocation is one of the most productive areas in evolutionary biology, with considerable interplay between theoretical and empirical work. However, observed sex ratios are often measured after developmental periods and they may not reflect primary sex investment ratios, which is what theory predicts. We examined with the sex ratio behaviour of the parasitoid wasp Melittobia, in which males do not disperse from their natal patch. In contrast with the well-supported predictions of local mate competition (LMC) theory, the extremely female-biased sex ratio observed at emergence changes little in response to ovipositing female number. We examined (1) the primary sex ratio at oviposition and (2) the pattern of male production over time, to test whether the inconsistency with LMC theory can be explained by differential developmental mortality between the sexes. We found that the sex ratio at oviposition measured with a microsatellite DNA marker did not differ from the sex ratio at emergence, indicating that differential developmental mortality is absent or weak. We also found that males were constantly produced throughout the period of oviposition after a single male was produced initially. © 2009 The Association for the Study of Animal Behaviour.